2016
DOI: 10.1111/jfbc.12292
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancing and Antioxidative Potentials of Velvet Beans (Mucuna pruriens) and Horseradish (Moringa oleifera) Seeds Extracts: A Comparative Study

Abstract: Velvet beans and Horseradish seeds are widely consumed as food, and use in folklore for the treatment of cognitive dysfunction although with limited information on their mechanisms of action. This study investigated and compared the effects of aqueous extracts of these seeds on the cholinergic [acetylcholinesterase (AChE) and butyrylcholinesterase (BChE)] and monoaminergic [monoamine oxidase (MAO)] enzymes and FeSO4‐induced thiobarbituric acid reactive species (TBARS) in isolated rat brain homogenate. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…High‐density lipoprotein cholesterol was determined using the method used by Adefegha et al. (). Low‐density lipoprotein cholesterol was determined using the method used by Oboh et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐density lipoprotein cholesterol was determined using the method used by Adefegha et al. (). Low‐density lipoprotein cholesterol was determined using the method used by Oboh et al.…”
Section: Methodsmentioning
confidence: 99%
“…Triglyceride concentration was determined according to the method used by Oboh, Bello, and Ademosun (2014). High-density lipoprotein cholesterol was determined using the method used by Adefegha et al (2017). Low-density lipoprotein cholesterol was determined using the method used by Oboh et al (2014).…”
Section: Experimental Designmentioning
confidence: 99%
“…Several studies have documented the in vitro free radical scavenging properties of legumes. Sowndhararajan, Siddhuraju, and Manian (), Zia‐Ul‐Haq, Ahmad, Amarowicz, and Feo (), and Adefegha et al () reported the abilities of Vigna vexillata , Vigna unguiculata and M ucuna pruriens to scavenge free radicals in vitro, respectively. They linked the antioxidant activities to the total phenolic contents.…”
Section: Discussionmentioning
confidence: 99%
“…An improved spectrophotometric method was used to determine the in vitro inhibitory activity of AChE and BChE . In 96‐well microplates, each group used three parallels, recorded with microphotometer board points.…”
Section: Methodsmentioning
confidence: 99%
“…25 In vitro AChE and BChE inhibition assay An improved spectrophotometric method was used to determine the in vitro inhibitory activity of AChE and BChE. 26 In 96-well microplates, each group used three parallels, recorded with microphotometer board points. The reaction mixture contained 140 μL phosphate buffer (pH 8.0), 20 μL solution under test and 20 μL AChE or BChE solution, 15 min reaction under 37°C.…”
Section: Synthesis Of Selected Peptidesmentioning
confidence: 99%